Proceedings of the SouthEast Conference 2017
DOI: 10.1145/3077286.3077294
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Neural Network-based Stock Trading System Using Technical Analysis and Big Data Framework

Abstract: In this paper, a neural network-based stock price prediction and trading system using technical analysis indicators is presented. The model developed first converts the financial time series data into a series of buy-sell-hold trigger signals using the most commonly preferred technical analysis indicators. Then, a Multilayer Perceptron (MLP) artificial neural network (ANN) model is trained in the learning stage on the daily stock prices between 1997 and 2007 for all of the Dow30 stocks. Apache Spark big data f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 9 publications
(8 reference statements)
0
20
0
2
Order By: Relevance
“…Technical analysis is usually used to predict short-to medium-term time horizons. An artificial neural network-based stock trading system using technical analysis and big data framework has been proposed in the work of [22]. The results have shown that, by choosing the most appropriate technical indicators, the neural network model can obtain comparable results against the buy and hold strategy in most of the cases.…”
Section: Deep Learning In Stock Predictionmentioning
confidence: 99%
“…Technical analysis is usually used to predict short-to medium-term time horizons. An artificial neural network-based stock trading system using technical analysis and big data framework has been proposed in the work of [22]. The results have shown that, by choosing the most appropriate technical indicators, the neural network model can obtain comparable results against the buy and hold strategy in most of the cases.…”
Section: Deep Learning In Stock Predictionmentioning
confidence: 99%
“…Sezer et al [25] proposed an artificial neural network that uses the technical analysis indicators such as MACD, RSI, Williams %R to predict Dow Jones 30 Stocks. Besides these approaches, evolutionary and genetic algorithms are used to forecast stock market prices and index in literature [1].…”
Section: Machine Learning and Evolutionary Solutionsmentioning
confidence: 99%
“…The hidden layer and an output layer which gives a single value as an output makes this system a multilevel perceptron regression. So internally the network regresses different independent input variable onto the single dependent variable by using equation 4 to compute the loss function [21]: (4) It is also clear by the formula that it's a squared error function, and α>0 is a non-negative hyper parameter that controls the magnitude of the penalty. Now coming to optimization according to gradient decent which is an algorithm for finding a minimum of the function or let's say optimization algorithm the gradient ∇LossW of the loss with respect to the weights is computed by equation 5: 5Where, i is the iteration step, and ε is the learning rate with a value larger than 0.…”
Section: Sentiment Analysismentioning
confidence: 99%